Risk Factors Associated with Prevalence of Zoonotic Tuberculosis in Small Ruminants in Chhattisgarh, India - Naik, Vivek K.; Shakya, Sanjay; Patyal, Anil; Ali, S. L.; Verma, Subhash K.; Hirpurkar, S. D.; Choudhary, Mamta; Chandrakar, Choodamani; Challagurugula, Raghupathi (International Journal of Bio-resource and Stress Management, 2024)
This study carried out in 2021-22 and 2022-23 at the College of Veterinary Science & A.H., Anjora, Durg, and ICAR-NIBSM, Baronda, Raipur, Chhattisgarh, India focused on examining molecular detection and determining risk factors associated with infections of Bovine tuberculosis (BTB) in small ruminants within the Chhattisgarh region. Zoonotic tuberculosis, a global threat emerging from the Mycobacterium tuberculosis complex, impacts humans, livestock, and wildlife. A total of 795 samples from small ruminants, including blood, aborted fetuses, vaginal swabs, and placental tissues, were collected. DNA extraction and multiplex PCR targeting Mycobacteria RD1 and RD4 genes were performed. Statistical analyses explored individual animal-level and herd-level risk factors using SPSS. Results revealed a 0.75% prevalence of BTB in Small ruminants. Herd-level analysis demonstrated 2.6% prevalence. The statistical analysis assessing individual animal-level risk factors associated with BTB prevalence showed no significant associations with species, age, sex, or sample type. Herd-level risk factors included the number of small ruminants (OR=1.158, p =0.003) and introducing new animals (OR=1.090, p=0.034). In a multivariable logistic regression analysis, the variable “Number of small ruminants kept” emerged as a significant predictor (OR=1.155, p=0.004).Other factors like vaccination, biosecurity measures, and history of reproductive disorders did not reach statistical significance. This study provides comprehensive insights into the multifaceted risk factors associated with zoonotic tuberculosis transmission in small ruminants. The findings underscore the importance of ongoing research to formulate effective control strategies considering the nuanced nature of BTB.